1996
DOI: 10.1002/ana.410400108
|View full text |Cite
|
Sign up to set email alerts
|

Language cortex representation: Effects of developmental versus acquired pathology

Abstract: Relatively little is known about language cortex representation in patients with developmental pathology and epilepsy. We report the results of mapping language by electrical stimulation of chronically implanted subdural electrodes in 34 patients (mean age, 12.2 years) evaluated for epilepsy surgery, 28 of whom had magnetic resonance imaging or histological evidence of developmental tumors or cortical dysplasia. Language cortex was identified in the temporal or frontal lobe of 19 patients (left hemisphere in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 23 publications
8
107
0
5
Order By: Relevance
“…On the contrary, the expected asymmetry of a left hemisphere dominance was preserved, in spite of distorted anatomic structures and in spite of significant morphometric changes. This finding is in accordance with an earlier electrophysiologic investigation of language organization in patients with epilepsy, 20 which demonstrated that developmental lesions do not displace language cortices from prenatally determined sites when the language cortex is structurally intact. Similar results of a preserved language dominance in the left hemisphere in patients with left temporal AC were reported in a PET study.…”
Section: Results Clinical Characterization Of Patientssupporting
confidence: 92%
“…On the contrary, the expected asymmetry of a left hemisphere dominance was preserved, in spite of distorted anatomic structures and in spite of significant morphometric changes. This finding is in accordance with an earlier electrophysiologic investigation of language organization in patients with epilepsy, 20 which demonstrated that developmental lesions do not displace language cortices from prenatally determined sites when the language cortex is structurally intact. Similar results of a preserved language dominance in the left hemisphere in patients with left temporal AC were reported in a PET study.…”
Section: Results Clinical Characterization Of Patientssupporting
confidence: 92%
“…These results support the theory of brain reorganization (neuronal plasticity) mentioned by Springer et al 10 and Janszky et al 28 , as well as the theory proposed by Duchowny et al 29 , stating that only damages on the first years of life result in consistent contralateral reorganization of language. Risse et al 30 emphasize that the incidence of atypical language is much more frequent in patients with a history of left hemisphere early lesions (from childhood).…”
Section: Language Hemisphere Dominance and Age At Epilepsy Onsetsupporting
confidence: 90%
“…In a study with refractory epilepsy patients, Duchowny et al 29 concluded that language transfer to the right hemisphere happens only in cases of lesions occurring before five years of age and in which the language cortex is destroyed, and not in cases of development lesions and epileptogenic discharges.…”
Section: Language Hemisphere Dominance and Age At Epilepsy Onsetmentioning
confidence: 99%
“…In patients with focal epilepsy the determination of eloquent cortices can be further complicated by a commonly observed anatomical alteration of the eloquent cortex, which is driven by at least two interacting factors: (1) The epileptogenic lesion itself is identical with or forms a large part of the anatomical alteration. This has been observed in lesions which originate from an early disturbance in the individual's development, such as prenatal or infant cerebral insults [23,24], cortical malformations or developmental tumors [25,26]. (2) An anatomical alteration of the eloquent cortex was also observed in patients with epileptogenic lesions remote to the eloquent cortex [27], suggesting that the seizures, interictal cortical activity or other functional abnormality of the cortex lead to alteration of functional localization [28].…”
Section: Discussionmentioning
confidence: 99%